Some Features of the Ionospheric Radio Wave Characteristics Over China Observed During the Solar Eclipse of 21 June 2020 - Chernogor, L. F.; Garmash, K. P.; Guo, Q.; Luo, Y.; Rozumenko, V. T.; Zheng, Y. (Radio science, 2022)
The Harbin Engineering University, the People's Republic of China, multifrequency multiple‐path coherent radio system operates continuously and provides data for post analysis. The data collected during the solar eclipse of 21 June 2020 have been chosen for this study with the objectives to interpret the variations in the Doppler spectra, Doppler shift, and in the reflected radio wave amplitudes that are associated with the solar eclipse, establish the magnitude and find physical significance of these variations, determine the reduction in the electron density caused by the solar eclipse, and to estimate an increase in wave activity in the ionosphere. The eclipse was accompanied by Doppler spectrum diffuseness resulting from an increase in the number of rays, the temporal variations in the Doppler shift were observed to be bi‐polar, asymmetrical, and anomalously small, with extreme Doppler shift magnitudes varying from −11 to −40 mHz and from 22 to 56 mHz. The duration of processes with negative Doppler shifts varied from 50 to 80 min, and the duration of processes with positive Doppler shifts changed from 30 to 80 min. The multi‐hop propagation (from two to five hops) took place along all propagation paths, with a 360 to 560‐km one‐hop length, due to the anomalous radio wave propagation via the sporadic‐E layer present about 80% of the time on 21 June 2020. The Doppler shift exhibited 4–18‐min period quasi‐sinusoidal variations with 20–10‐mHz amplitudes. Plain Language Summary In the past, the study of the influence of eclipses on the ionosphere seemed to be a rather simple subject because a solar eclipse seemed to be just mimicking night, although over a shorter time interval. Subsequently, the movement of the solar terminators has been discovered to generate atmospheric gravity waves, which is also true for eclipses. Recent advances in instrumentation and measurement techniques have facilitated the revelation of unusual and interesting phenomena that do not necessarily belong to nighttime conditions. For example, in this study, we have discovered, along with the determination of specific changes in the atmospheric and radio wave parameters, that temporal variations in the Doppler shift were bi‐polar, asymmetrical, and anomalously small. Key Points Doppler shift variations were bi‐polar, asymmetrical, and anomalously small, with extremes varying from −11 to −40 MHz and from 22 to 56 MHz Multi‐hop propagation (from two to five hops) took place along all propagation paths, with a length of one hop varying from 360 to 560 km An electron density decrease was determined to vary from –(12–16)% to –(20–26)% along different propagation paths